Achieving substantive justice in mediation through procedural justice: An illusory or realizable goal? - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2018)
Mediation has been plagued with a problem of legitimacy. Genn stated that mediation “does not contribute to substantive justice because mediation requires the parties to relinquish ideas of legal rights during mediation and focus, instead, on problem-solving”. Mediation appears to be all about procedural justice, a concept that is associated with perceptions of fair treatment. And procedural justice does not seem to have any discernible link with substantive justice, in terms of giving effect to well-accepted norms.This blog entry is drawn from a paper that was presented at the Australasian Dispute Resolution Research Network 6th Annual Roundtable and the LSAANZ Conference. I argue that there is an invaluable connection between procedural and substantive justice that should be further articulated and strengthened. However, there are also considerable inadequacies in the current mediation principles, causing weak links between procedural and substantive justice. I focus here on only one aspect of the paper – that the mediation principle of “norm education” should be further developed to enhance party autonomy and more adequately advance substantive justice.